Analysis of Factors Affecting Economic Growth and Poverty in Nigeria: A Panel Data Approach - Kehinde Emmanuel Agbeni; Charity Okonkwo Chukwu; Anya Adebayo Anya; Mercy Oluwabusayo Donatus (SMARTINDO, 2025)
Purpose - This study examines the key factors influencing economic growth and poverty reduction in Nigeria, with a focus on investment, government spending, exchange rates, infrastructure, and population dynamics. It explores how these variables interact to shape poverty outcomes in the Nigerian context. Design/methodology/approach - The study employs panel data regression analysis using secondary data from the Central Bank of Nigeria, World Bank Development Indicators, and National Bureau of Statistics, covering 1990–2022. Path analysis was used to capture both direct and indirect effects. Key regression results show that investment significantly drives GDP growth (β = 0.312, p < 0.05), while government spending positively impacts poverty reduction through its effect on output. However, population growth exerts pressure on poverty levels, weakening the gains from GDP growth. Originality - Unlike previous studies that often treat growth and poverty separately, this paper integrates the two, offering fresh empirical insights into how macroeconomic variables simultaneously influence Nigeria’s growth-poverty nexus. Findings and Discussion - The findings indicate that expansion in investment and infrastructure improves growth outcomes, which in turn reduce poverty. For example, the regression shows that a 1% increase in investment raises GDP by 0.35%, while a 1% rise in government expenditure reduces poverty incidence by 0.22%. Yet, persistent exchange rate fluctuations and high population growth counter these gains, limiting poverty reduction. Conclusion - The study concludes that targeted investment, stable fiscal policies, and stronger infrastructure development are essential to accelerate growth and achieve poverty reduction in Nigeria. Policy reforms should address population pressures and exchange rate instability to ensure sustainable economic progress.